A STUDY OF EMOTIONAL INTELLIGENCE OF PRIMARY TEACHERS IN RELATION TO GENDER, SCHOOL TYPE & TEACHING EXPERIENCE - Dr.Shashi Chaudhary (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In the present research study, emotional intelligence have been studied with reference to the gender, school type and teaching experience of primary teachers. In this study Gender have male & female , School Type have government & non-government and Teaching experience of teachers was divided into four category: first category (less than 5 years of teaching experience), second category (5-15 years of teaching experience), third category (16-25 years of teaching experience), fourth category (more than 25 years of teaching experience) . A total of 800 teachers working in primary schools have been selected for sample through random method.